Pengembangan Alat Kunci Pintu Selenoid Menggunakan Rangkaian Penurun Arus - Era Fajira (Jurnal Pendidikan Fisika dan Sains, 2020)
This study aims to determine the working principle of the current reducing circuit on the selenoid door lock so that it can function. The current reducing circuit is in the form of a simple power supply in the form of an AC current that has a reduced voltage. The current reducing circuit consists of a voltage reducer, a rectifier circuit, and a filter circuit. When the circuit is given an AC current and then converted to a DC current with a voltage of 12 V to make the selenoid door lock work. Selenoid door lock work systems, namely Normally Close (NC) and Normally Open (NO). if given a selenoid voltage will elongate (closed), while the way it works is NOT the opposite of NC. The research method used is Research and Development, with the 4D model. In this development model only uses 3 stages, namely defining, designing, and developing. Data collection techniques used were instrument validation in the media and teaching materials. The results obtained from media experts amounted to 74.29%, while the results from material experts amounted to 75%. From the percentage based on the scale used is the Likert scale, then the media and teaching materials are declared valid (can be used, with several revisions), so it can be concluded that the media and teaching materials can be used as learning media.